Perceptions of illness in Hemodialysis Patients in the Reproductive Age Group: A cross-sectional study - Afriyanti, Esi; Febri Krisdianto, Boby; Hafifa Transyah, Chichi (Universitas Aisyah Pringsewu, 2023)
Background: The prevalence of hemodialysis patients continues to increase, especially in the productive age group, where these individuals are important contributors to the workforce. Compliance with hemodialysis greatly influences patient productivity, has a direct impact on morbidity and mortality rates. Therefore, cultivating positive perceptions is very important, especially with regard to patient characteristics. The aim of this research is to examine the interplay between patients' perceptions of illness and the associated characteristics in hemodialysis patients within the productive age groupMethods: This research is a cross-sectional quantitative study that involved 191 purposively sampled respondents. Data collection utilized a questionnaire encompassing demographic information, and patients' perceptions of their illness were evaluated through the Brief Illness Perception Questionnaire (B-IPQ). The analysis employed the Mann-Whitney U and Kruskal Wallis H tests, with the significance level set at p0.05.Results: The findings indicated an average perception value of 58.53 ± 8.455. A significant relationship exists between the perception of hemodialysis patients and variables such as age, gender, education level, occupation, duration of hemodialysis, and comorbidities (p0.05).Conclusion: The findings of this study revealed a correlation between hemodialysis patient perceptions and their individual characteristics. Consequently, healthcare professionals, with a special emphasis on nurses, should employ a personalized approach to effectively shape positive patient perceptions. This tailored approach should consider individual characteristics due to the diverse needs of patient.